Lessons From High Inflation Epidsodes for Stabilizing the Economy in Zimbabwe - Clausen, Jens (IMF Working Papers; Working Paper ;, 2007)
Zimbabwe has currently the highest rate of inflation in the world (an annual rate of 1,730 percent in February, 2007). The high rates of inflation have contributed to the contraction of the economy, which has declined by about 30 percent since 1999. This paper examines the stabilization experience of countries that experienced similar rates of inflation (above 1,000 percent) during 1980-2005 and draws lessons for Zimbabwe. First, with appropriate stabilization policies, the fall in inflation can be very rapid and output normally recovers within the first year or two of stabilization. Second, while reforms need to be comprehensive, a strong upfront fiscal consolidation, including elimination of quasi-fiscal activities, is a critical element of a successful stabilization program. Third, although stabilization itself can be done without significant external financing in the first year, most countries benefited from external policy advice and technical support, including from the IMF, during stabilization and from an increase in financial assistance in subsequent years.